COVARYING SEDIMENTARY AND BIOTIC FLUCTUATIONS IN LOWER-MIDDLE EOCENE PYRENEAN DEEP-SEA DEPOSITS: PALAEOENVIRONMENTAL IMPLICATIONS - Payros A.; Orue-Etxebarria X.; Pujalte V. (My University, 2006)
Analyses of expanded (1975 to 3330 m thick) deep-marine Ypresian-Lutetian successions from the Pamplona and Basque basins (W Pyrenees) demonstrate a recurring pattern of coeval sedimentary and biotic changes: intervals rich in resedimented deposits are typified by high-latitude planktonic foraminiferal indices, whereas intervals devoid of large-scale resedimented deposits (megabreccias) are characterized by low-latitude planktonic foraminiferal indices. Data from the megabreccia-free intervals record a reasonably good correlation between the vertical trend of planktonic foraminiferal indices from the two Pyrenean basins and the global curve of oxygen isotopes from deep-sea records. For instance, the Early Eocene Climatic Optimum and the long-lasting late Ypresian-Lutetian cooling are respectively recorded in the studied successions by an increase and by a progressive decline in abundance in low-latitude planktonic foraminiferal indices. This correlation may support the assumption that changes of planktonic foraminiferal indices in the megabreccia-free intervals were forced by global climatic changes. The dominance of high-latitude planktonic foraminiferal indices in the megabreccia-bearing intervals is more difficult to interpret. Such dominance might record global cooling episodes that resulted in eustatic lowstand resedimentation events. However, the climatic cooling and sea-level fall do not fully explain the characteristics of these intervals. A reasonable scenario is that tectonically induced resedimentation processes resuspended large volumes of mud and organic matter, which led to the eutrophication of seawater. Such eutrophication would preferentially affect low-latitude oligotrophic planktonic foraminiferal species and lead to a relative or absolute increase in the cosmopolitan opportunistic species that typify high-latitude groups. © 2005 Elsevier B.V. All rights reserved.
Keywords: CLIMATE; EOCENE; EUTROPHICATION; MEGABRECCIA; PLANKTONIC FORAMINIFERA; RESEDIMENTATION; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен